2013
DOI: 10.1002/bip.22241
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the structures of alanine tri‐ and tetra‐peptides with antiparallel β‐sheet assessed by X‐ray diffraction, solid‐state NMR and chemical shift calculations by GIPAW

Abstract: Alanine oligomers provide a key structure for silk fibers from spider and wild silkworms.We report on structural analysis of L-alanyl-L-alanyl-L-alanyl-L-alanine (Ala)4 with anti-parallel (AP) β-structures using X-ray and solid-state NMR. All of the Ala residues in the (Ala)4 are in equivalent positions, whereas for alanine trimer (Ala)3 there are two alternative locations in a unit cell as reported previously (Fawcett and Camerman, Acta Cryst., 1975, 31, 658-665). (Ala)4 with AP β-structure is more stable tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 18 publications
3
49
1
Order By: Relevance
“…Figure (C) and (D) show 1D 1 H spectra of P‐ and AP‐Ala 3 including three 1 H peaks of CH 3 , CH, and NH/NH 3 + . The detailed assignment of 1 H chemical shift of P‐ and AP‐Ala 3 and the structural information were reported in the previous study ,. Here, the protons of CH 3 , CH, NH, and NH 3 + refer to 1 H β , 1 H α , 1 H NH , and 1 H NH3 + .…”
Section: Resultsmentioning
confidence: 83%
“…Figure (C) and (D) show 1D 1 H spectra of P‐ and AP‐Ala 3 including three 1 H peaks of CH 3 , CH, and NH/NH 3 + . The detailed assignment of 1 H chemical shift of P‐ and AP‐Ala 3 and the structural information were reported in the previous study ,. Here, the protons of CH 3 , CH, NH, and NH 3 + refer to 1 H β , 1 H α , 1 H NH , and 1 H NH3 + .…”
Section: Resultsmentioning
confidence: 83%
“…It is found that there are multi diffraction peaks in the spectra. The diffraction peaks with d spacing of 3.01–3.04 Å were detected in both oligopeptide‐decorated samples, which should be assigned to the hydrogen spacing in a β‐sheet structure . Typically, the disordered structures will induce the augment of hydrogen bonds spacing .…”
Section: Methodsmentioning
confidence: 92%
“…As acomparison, randomly functionalized polyisoprene (R-OH-PIP) without at erminal polar block was also prepared by tuning the feeding sequence of monomers (Scheme 1). [28] Typically,t he disordered structures will induce the augment of hydrogen bonds spacing. Themolecular weights of two samples are high enough to ensure the mechanical properties.…”
mentioning
confidence: 99%
“…[28] Typically,t he disordered structures will induce the augment of hydrogen bonds spacing. [28] Typically,t he disordered structures will induce the augment of hydrogen bonds spacing.…”
mentioning
confidence: 99%
See 1 more Smart Citation